2014
DOI: 10.3109/13880209.2013.876053
|View full text |Cite
|
Sign up to set email alerts
|

Allicin enhances chemotherapeutic response and ameliorates tamoxifen-induced liver injury in experimental animals

Abstract: Context: Tamoxifen (TAM) is widely used for treatment of hormone-dependent breast cancer; however, it may be accompanied with hepatic injury. Allicin is the most abundant thiosulfinate molecule from garlic with the potential to provide beneficial effects on various diseases. Objective: To elucidate the effect of commercially available allicin on both antitumor activity and liver injury of TAM. Materials and methods: The cytotoxicity of TAM and/or allicin was evaluated in vitro using cultured Ehrlich ascites ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In view of the results of the current study there is a significant increase in the level of serum Lipids when treated with TAM and elevation increased as the dose multiplied increased by the level of (30, 40, 50)mg/kg compared to the control group and this is consistent with [10][11][12][13].…”
Section: Discussionsupporting
confidence: 77%
“…In view of the results of the current study there is a significant increase in the level of serum Lipids when treated with TAM and elevation increased as the dose multiplied increased by the level of (30, 40, 50)mg/kg compared to the control group and this is consistent with [10][11][12][13].…”
Section: Discussionsupporting
confidence: 77%
“…However, SAMC was shown to markedly suppress the cisplatin-induced elevation in the level of inflammation cytokines including TNF-, IL-1, TGF1, COX-2 and iNOS clearly indicating that SAMC exerted an anti-inflammatory effect in cisplatin-induced renal injury as well as hepatotoxicity in rat model (Xiao et al, 2013;Zhu et al, 2017). Suddek, 2014Zheng et al, 1997Miron et al, 2003;Zhang et al, 2010;Chu et al, 2012;Wang et al, 2012;Lee et al, 2013 Suddek, 2014Zheng et al, 1997Miron et al, 2003;Zhang et al, 2010;Chu et al, 2012;Wang et al, 2012;Lee et al, 2013 162.26 Diallyl thiosulfinate (Allicin) 2. Siegers et al,1999 161.22 Alliin 1.…”
Section: Aged Garlic Extractmentioning
confidence: 99%
“…A study of Suddek (2014) revealed that the pre-treatment with allicin potentiates the antitumor effect of tamoxifen and protects animals against hepatic injury by preventing oxidative stress and lipid peroxidation, enhancing antioxidant enzyme activities and inhibiting hepatic inflammation.…”
Section: Fresh Garlicmentioning
confidence: 99%
“…Mice treated with 250 μg of ajoene had only 4.9 % the number of tumours per mouse compared with the control group at 18 weeks. Tamoxifen (TAM) combination with allicin (5 or 10 μM) showed a signifi cant cytotoxic effect compared with the TAM-treated group as manifested by a decrease in the percent survival of Ehrlich ascites carcinoma to 35 % and 29 %, respectively (Suddek 2014 ). Allicin (10 mg/kg, orally) enhanced the effi cacy of TAM (1 mg/kg, i.p.)…”
Section: Animal Studiesmentioning
confidence: 99%